Association of metformin, aspirin, and cancer incidence with mortality risk in adults with diabetes. Issue 2 (1st March 2023) - Orchard, Suzanne G; Lockery, Jessica E; Broder, Jonathan C; Ernst, Michael E; Espinoza, Sara; Gibbs, Peter; Wolfe, Rory; Polekhina, Galina; Zoungas, Sophia; Loomans-Kropp, Holli A; Woods, Robyn L; ,
Abstract: Background: Metformin and aspirin are commonly co-prescribed to people with diabetes. Metformin may prevent cancer, but in older people (over 70 years), aspirin has been found to increase cancer mortality. This study examined whether metformin reduces cancer mortality and incidence in older people with diabetes; it used randomization to 100 mg aspirin or placebo in the ASPirin in Reducing Events in the Elderly (ASPREE) trial to quantify aspirin's impact on metformin users. Methods: Analysis included community-dwelling ASPREE participants (aged ≥70 years, or ≥65 years for members of US minority populations) with diabetes. Diabetes was defined as a fasting blood glucose level greater than 125 mg/dL, self-report of diabetes, or antidiabetic medication use. Cox proportional hazards regression models were used to analyze the association of metformin and a metformin-aspirin interaction with cancer incidence and mortality, with adjustment for confounders. Results: Of 2045 participants with diabetes at enrollment, 965 were concurrently using metformin. Metformin was associated with a reduced cancer incidence risk (adjusted hazard ratio [HR] = 0.68, 95% confidence interval [CI] = 0.51 to 0.90), but no conclusive benefit for cancer mortality (adjusted HR = 0.72, 95% CI = 0.43 to 1.19). Metformin users randomized to aspirin had greater risk of cancer mortality compared with placebo (HR = 2.53, 95% CI = 1.18 to 5.43), but no effect was seen for cancer incidence (HR = 1.11, 95% CI = 0.75 to 1.64). The possible effect modification of aspirin on cancer mortality, however, was not statistically significant (interaction P  = .11). Conclusions: In community-dwelling older adults with diabetes, metformin use was associated with reduced cancer incidence. Increased cancer mortality risk in metformin users randomized to aspirin warrants further investigation. ASPREE Trial Registration: ClinicalTrials.gov ID NCT01038583